Trade Facilitation, R&D Innovation, and Export Sophistication of Manufacturing Industries: Evidence from Russia and Central-Eastern European Countries - Yuanhong Hu (Shanghai University of Finance and Economics, 2020)
This paper calculates the trade facilitation index and manufacturing export sophistication of Russia and Central and Eastern European countries from 2003 to 2017, and examines the impact of trade facilitation and R&D innovation on manufacturing export sophistication. The study found that the export sophistication of labor-intensive industries continues to decrease, the export sophistication of capital and technology-intensive industries continues to increase, while the export sophistication of traditional resource-based heavy industries is stable. In addition, trade facilitation and R&D innovation have significantly contributed to the export sophistication of Russia, Central and Eastern European countries, especially the manufacturing industry after the 2009 financial crisis. For Central European and European Union member states, the impact of trade facilitation and R&D innovation on export sophistication is significantly greater than that of Eastern European and non-EU member states. The promotion of heavy, heterogeneous, medium and high-tech industries is obviously stronger than that of light, homogeneous and low-tech industries. In addition, the moderating role of trade dependence cannot be ignored. Trade facilitation and R&D innovation have a significant non-linear impact on export sophistication.
Keywords: F14; F41; F43; 330; Trade Facilitation; Export Sophistication; R&D Innovation; Manufacturing; Russia; Central and Eastern Europe